Implementasi Keputusan Tata Usaha Negara dalam Penyelesaian Sengketa Proses Pemilihan Umum di Provinsi Nusa Tenggara Barat - Khulud Miftahul Zanah (Uniku Law Review, 2025)
The purpose of this article is to determine the regulations or substance of the settlement of general election disputes in the province of West Nusa Tenggara, as well as to determine how effective the implementation of the State Administrative Decree is in resolving general election disputes in the province of West Nusa Tenggara. This article uses a normative juridical method or commonly known as library research which emphasizes the approach and analysis of laws and regulations, legal doctrines and court decisions as guidelines for individuals in behaving in the community. Indonesia is a country based on democracy, as stated in Article 1 paragraph (3) of the 1945 Constitution. Evidence that Indonesia is a democratic country is reflected in the process of holding general elections with integrity. However, of course, in its implementation, general elections often arise disputes or dissatisfaction with the process and results of the implementation of general elections. Therefore, as a response to the existence of general election disputes, an institution and mechanism are needed to resolve general election disputes, either through the Constitutional Court, Bawaslu and the State Administrative Court. Regarding the authority of the State Administrative Court to resolve general election disputes as one of the disputes related to state administrative decisions disputes based on Law Number 5 of 1986 in conjunction with Law Number 5 1 of 2009 concerning State Administrative Courts. The implementation or application of the authority of the State Administrative Court can be seen from one of the Decisions Number 124/G/2025/PTUN.JKT.